Resilience among secondary school students in South-Western Nigeria; association with abuse and neglect (2018)
Introduction: Resilience, which aids coping and adjustment, prevents the development of mental health issues for individuals exposed to adversities. Abuse and neglect are some of the adversities that affect the health of adolescents. This study examined the relationship between abuse, neglect and resilience of adolescents. Methods: The study adopted a cross-sectional design among 522 secondary school adolescents using interviewer-administered semi-structured questionnaires. Information on socio-demographics, abuse, neglect and resilience were elicited. Associations were tested with significance set at 5%. Results: The mean age of respondents was 15.9 ± 1.5, 301 (57.7%) were females and 144 (27.6%) were from polygamous homes. Two hundred and forty-three (46.4%) had high resilience, 141 (27.0%) moderate resilience and 138 (26.6%) had low resilience. Psychological, physical and sexual abuse were reported among 238 (45.7%), 168 (32.1%) and 45 (8.6%) adolescents, respectively, while 71 (13.6%) and 134 (25.8%) experienced psychological and physical neglect, respectively. Adolescents who experienced physical abuse and sexual abuse were about 2 and 2.5 times less likely, respectively, to have high resilience than those who did not experience physical and sexual abuse. Conclusion: Abuse and neglect negatively influence resilience of adolescents. Interventions targeted at reducing abuse and neglect should be incorporated in adolescent health protocols to increase their resilience.